Analysis of Ploidy in Hypopharyngeal Cancer by Laser Scanning Cytometry on Fine Needle Aspirate Biopsies - Andreas O.H. Gerstner; Julia Machlitt; Hans‐Jürgen Welkoborsky; Friedrich Bootz; Attila Tárnok (Analytical Cellular Pathology)
Aim To test laser scanning cytometry (LSC) for the analysis of ploidy in squamous cell carcinoma of the hypopharynx (SCCH) and to develop a routine application for minimal samples such as fine needle aspirate biopsies (FNABs). Methods: From 11 individuals 30 FNABs of primary tumors (n=11) and lymphatic metastases of SCCH (n=11) and non‐metastatic lymph nodes (n=8) are analyzed by LSC. This microscope based instrument scans the cells after immobilization on a glass slide and after double staining of cytokeratin and DNA. The location of each cell is stored with the fluorescence data. Therefore the morphology of every cell can be documented by re‐staining with H&E and re‐localization on the slide. Additionally, aliquots are Feulgen‐stained for image cytometry in 8 specimens. Results: The diploid reference peak is identified taking leukocytes as internal standard. The DNA‐index of the carcinoma cells ranges from 0.4 to 3.8. Comparison with image cytometry shows good correlation (r=0.89). Conclusion: LSC provides a reliable and objective way to determine the ploidy of SCCH pre‐operatively. Colour figures can be viewed on http://www.esacp.org/acp/2003/25‐2/gerstner.htm.